2017
DOI: 10.3390/ijerph14050475
|View full text |Cite
|
Sign up to set email alerts
|

Stress in School. Some Empirical Hints on the Circadian Cortisol Rhythm of Children in Outdoor and Indoor Classes

Abstract: This prospective longitudinal survey compared the stress levels of students taught using an outdoor curriculum in a forest, with children in a normal school setting. We were especially interested in the effect outdoor teaching might have on the children’s normal diurnal cortisol rhythm. 48 children (mean age = 11.23; standard deviation (SD) = 0.46) were enrolled, with 37 in the intervention group (IG), and 11 in the control group (CG). The intervention consisted of one full school day per week in the forest ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 41 publications
5
78
0
2
Order By: Relevance
“…According to these analysis, the results of cortisol and cfDNA regarding the peak reactivity and AUCi are diverse. First, we could partially confirm our previously reported results [8] reflecting their independence of the analysis methodology, as students' cortisol levels were not affected by the relative amounts of MVPA in the IG. However, in the CG, the relative amount of MVPA is more likely to exert a lowering effect on the cortisol PR; the more active the students were in MVPA levels, the more their cortisol levels seemed to decrease.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…According to these analysis, the results of cortisol and cfDNA regarding the peak reactivity and AUCi are diverse. First, we could partially confirm our previously reported results [8] reflecting their independence of the analysis methodology, as students' cortisol levels were not affected by the relative amounts of MVPA in the IG. However, in the CG, the relative amount of MVPA is more likely to exert a lowering effect on the cortisol PR; the more active the students were in MVPA levels, the more their cortisol levels seemed to decrease.…”
Section: Discussionsupporting
confidence: 81%
“…However, we believe that our study can provide valuable insights into the EOtC research, health promotion in schools, and the assessment and analysis of cortisol, cfDNA, SB, and PA in the educational setting. In our previous study [8], we reported a statistically significant difference in the measured cortisol levels between the CG and IG; regular teaching in the forest correlated with a lower cortisol secretion at noon compared with the standard indoor teaching, and this association was independent of students' MVPA levels. Considering the compositional nature and, thus, the codependency of students' SB, LPA, and MVPA, we elucidated students' cortisol values during school time in this study.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…La recherche sur l'enseignement en dehors de la salle de classe -une technique d'enseignement intégrant périodiquement la nature, mise au point en Scandinavie [11,68] est unanime pour dire que dans les environnements naturels, cette méthode favorise invariablement des niveaux d'activité physique modérée à vigoureuse plus élevés, comparée aux méthodes classiques en salle [30,49,91,92,138]. De plus, on observe que le taux de cortisol chez ces enfants (indicateur de stress) diminue au cours d'une journée d'enseignement de ce type dans un environnement naturel, alors qu'il demeure inchangé sur une journée d'enseignement classique en salle [30].…”
Section: • Ce Qui Est Probable Ce Qui Justifie D'avoir Une Confianceunclassified